Robot para cirugía laparoscópica - Minor, A; Mosso, J. L.; Domínguez, A.; Martínez, R. C.; Muñoz, R.; Lara, V. (Revista Mexicana de Ingenieria Biomedica, 2002)
This work describes a laparoscopic surgery robot design. The characteristics and principal electronic and clinical criteria that should be considered for this type of surgery are presented. The designed robot was experimentally tested in the IPN Medicine School, doing thoracoscopy and laparoscopy procedures in dogs. In the experiments, the robot was used as surgeon assistant for laparoscopic manipulation, inside the abdominal and thoracic cavity.